L’accompagnement de l’apprentissage en entreprise et développement de l’agentivité. Le cas des apprenti-e-s en automatisation en Suisse - Alexandra Felder; Isabelle Caprani; Kerstin Duemmler (Éducation et Socialisation)
Based on qualitative research on training experience of automation technology apprentices in Switzerland, this paper analyses the relationship between workplace guidance and the development of agency. The case study of four industrial companies shows that guidance has an influence on the form of agency that young people in VET develop on the workplace. In a context of guidance characterized by a strong relationship with the training person, expansive participation in company’s activities and adapted structuring interventions, apprentices engage directly in the optimization of learning processes and take on responsibilities within the community of practices. Apprentices who experience poorly adapted or insufficient guidance feel that they are not learning their trade well and fear failure in exams. Nevertheless, these young people also develop intentionality and reflection towards the optimization of learning, whereas their action is focused on improving learning conditions.